High-throughput, deterministic single cell trapping and long-term clonal cell culture in microfluidic devices. Issue 4 (18th December 2014) - Chen, Huaying; Sun, Jane; Wolvetang, Ernst; Cooper-White, Justin
Abstract : In this paper, the design, development and validation of a novel high throughput microfluidic device enabling both the robust and rapid trapping of 100's to 1000's of single cells and their in situ clonal growth is described. Abstract : We report the design and validation of a two-layered microfluidic device platform for single cell capture, culture and clonal expansion. Under manual injection of a cell suspension, deterministic trapping of hundreds to thousands of single cells (adherent and non-adherent) in a high throughput manner and at high trapping efficiency was achieved simply through the incorporation of a U-shaped hydrodynamic trap into the downstream wall of each micro-well. Post single cell trapping, we confirmed that these modified micro-wells permit the attachment, spreading and proliferation of the trapped single cells for multiple generations over extended periods of time (>7 days) under media perfusion. Due to its a) low cost, b) simplicity in fabrication and operation, c) high trapping efficiency, d) reliable and repeatable trapping mechanism, e) cell size selection and f) capability to provide perfused long-term culture and continuous time-lapse imaging, the microfluidic device developed and validated in this study is seen to have significant potential application in high-throughput single cell quality assessment and clonal analysis.